Ion temperature and delta B effects on ULF fluctuations at the magnetopause - Pillay, R.; Bharuthram, R.; Lakhina, G.S. (My University, 1996)
In this paper, we present an extension of the work by Lakhina, Shukla and Stenflo (Geophys. Res. Lett. 20, 2419 1993) on the generation of ultralow frequency (ULF) fluctuations at the earth's magnetopause. A high beta model for the generation of these short wavelength fluctuations is described. In this model, drifts due to density and magnetic field gradients, present at the magnetopause, act as free energy sources for the excitation of the ULF waves. The model also considers both warm electrons and ions and is based on the SS equations (Shukla and Stenflo. J. Exp. Theor. Phys. 57, 692 1993) for low-frequency EM waves in non-uniform high beta magnetoplasmas. Using fluid theory the associated dispersion relation is first established, then numerically solved for unstable modes in different regions of parameter space.
Keywords: Ultralow frequency fluctuation; Magnetopause